NAVIGATING CHALLENGES: STUDENT TEACHERS’ EXPERIENCES IN TEACHING ENGLISH TO YOUNG LEARNERS AT KAMPUS MENGAJAR - Apriani, Meissy Anis; Kurniawan, Dedy; Anastasia, Indri (Universitas Teknokrat Indonesia, 2025)
This qualitative research aims to describe the challenges faced by student teachers from the English Department during the Kampus Mengajar program and the strategies they employed to overcome those challenges. The study utilized a qualitative method with a case study approach to conduct an in-depth investigation. The research involved four participants, with two enrolled in Kampus Mengajar Batch 6 and the other two in Batch 7. Data were collected through semi-structured interviews with the participating student teachers and supporting documentation. Thematic analysis by Braun and Clarke was employed to analyze the data. The findings revealed that participants encountered several challenges while teaching English to young learners, which were categorized into challenges arising from the school environment and those stemming from the student teachers themselves. The study also identified various strategies used to address these challenges, including self-management strategies, strategies tailored to student characteristics, and varying teaching strategies. Additionally, the findings suggested that student teachers require guidance from lecturers to ensure that the strategies they implement align with the demands of Teaching English to Young Learners (TEYL) coursework.